Risk Factors for Declined Functional Status within 30 days After Elective Surgeries in Elderly Patients: A Prospective Cohort Study - Yudo Murti Mupangati; Henry Setyawan; Czeresna Heriawan Soejono; Muhammad Hussein Gasem; Ignatius Riwanto (Interna Publishing, 2023)
Background: Older adults are at risk of decreasing functional status due to their condition and many factors. Although many studies have been conducted about declining in functional status, based on the author's knowledge, only this study that has conducted about functional status changes in the elderly involving the frailty status which undergoing surgery in Indonesia. There are many factor was postulated, some of that was checked routine and applicable in clinical practice. Furthermore, identification of these risk factors can be used a basis for decision making to perform surgeries in older adults because poor functional status causes declining quality of life in the elderly patients. The aim of this research was to determine the risk factors for declined functional status within 30 days after elective surgeries in elderly patients. Methods: We conducted a prospective cohort study from July 2021 to December 2021 at Dr. Kariadi Hospital, Semarang, Indonesia. We included patients aged 60 or older who underwent elective surgery under general anesthesia. We excluded those who underwent emergency surgery, day care surgery, or were unwillingness to participate. The functional status were assessed using the ADL (Activity of Daily Living) Barthel index. To identify risk factors of  declined ADL scores, a logistic regression analysis was performed on the age variable, gender, body mass index, frailty status, postoperative complications, as well as haemoglobin, and albumin levels. Results: This study included 191 participants, with 97 women (50.79%) and 94 men (42.21%). Declined in functional status within 30-days after surgery occurred in 54 participants (28.2%). There was a significant changed of functional status before and after surgery. Multivariate analysis showed that independently significant variables for declined functional status were male sex (OR 4.48, p value < 0.001), hypoalbuminemia (OR 2.59, p value 0.02), preoperative functional status (OR 2.37; p value 0.05), and postoperative complications (OR 24.885; p value < 0.001). Conclusion: Risk factors for declined functional status within 30 days after elective surgery in older patients are postoperative complications, preoperative functional status, hypoalbuminemia, and male gender.